ASERA: Brief histor(y/ies) - White, R; Gardner, P; Carr, M; Jones, A; Appleton, K; Fleer, M; Redman, C; Dawson, V; Chang, W; Ritchie, S (2009)
This collection of historical accounts provides diverse perspectives on the structure and culture of the community of researchers who participate in activities of the Australasian Science Education Research Association (ASERA). It describes the formation of the Association, and identifies major changes and challenges for the ever growing and internationalisation of its membership. © 2008 Springer Science+Business Media B.V.